2017
DOI: 10.3823/2400
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of People with Diabetes Mellitus Assisted in an Outpatient Follow-up Clinic

Abstract: Objective: To characterize the profile of people with diabetes, according to sociodemographic, clinical and laboratory variables. Method:Cross-sectional study with a quantitative approach, conducted with 110 people with diabetes mellitus treated at an outpatient follow-up clinic of a teaching hospital in João Pessoa -PB, Brazil, from February to June/2015. A form contemplating sociodemographic, clinical and laboratory variables was used for data collection. As for the analysis, descriptive statistics was used,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
3
0
2
Order By: Relevance
“…13 Self-care is strengthened by the presence of a partner to share care with treatment, increasing the chances of success in treatment. 11 It should be noted that this research presented a worrying finding, since half of the individuals investigated received up to a minimum wage, insufficient income for the basic maintenance of the elderly, 14 since, from the moment of retirement, this has significant financial loss, compromising their ability to maintain the necessary care for good nutrition, use of medicines, periodic examinations, factors that compromise the preservation of health and, therefore, control of the disease. 15 It is recalled that among people with diabetes, 3/4 live in low-to middle-income countries, 3 and, for the elderly population, one study found a statistically significant association between diabetes and low educational and income levels.…”
Section: Objective Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…13 Self-care is strengthened by the presence of a partner to share care with treatment, increasing the chances of success in treatment. 11 It should be noted that this research presented a worrying finding, since half of the individuals investigated received up to a minimum wage, insufficient income for the basic maintenance of the elderly, 14 since, from the moment of retirement, this has significant financial loss, compromising their ability to maintain the necessary care for good nutrition, use of medicines, periodic examinations, factors that compromise the preservation of health and, therefore, control of the disease. 15 It is recalled that among people with diabetes, 3/4 live in low-to middle-income countries, 3 and, for the elderly population, one study found a statistically significant association between diabetes and low educational and income levels.…”
Section: Objective Introductionmentioning
confidence: 87%
“…In another study on DM, the prevalence of chronic complications in most of the research participants. 11 It was stated that most of the elderly with T2Ds do not use tobacco, although smoking is considered a risk factor for T2D, 12 however, since the participants are elderly, there were no questions if, at some point in their life, they maintained the habit of smoking. It is exposed that research performed with elderly people with DM in the Family Health Strategy in Recife, Pernambuco, Brazil, was in agreement with this finding, representing 56.8% of its non-smoker sample.…”
Section: Methodsmentioning
confidence: 99%
“…quality of life. 13 Participants were at risk for cardiovascular complications. It is worth noting that, in relation to the time of DM, individuals had, for the most part, a diagnosis time of less than five years.…”
mentioning
confidence: 99%
“…122 Em relação ao estado civil, mais da metade dos indivíduos relatou ser casado, perfil semelhante a outros estudos na mesma população. 108,[116][117]123 Indivíduos casados apresentam 145 % mais chance de adesão ao tratamento e menores taxas de mortalidade. 119,124 Nessa perspectiva, o suporte familiar é fundamental ao controle da HA e do DM, sendo um aliado na aquisição de orientações de saúde adequadas e no enfrentamento da doença, principalmente no que tange à adesão de dieta com restrição de sódio e gorduras.…”
Section: Validação Clínica Dos Diagnósticos De Enfermagem E Seus Indi...unclassified
“…[127][128] A maioria da população desse estudo relatou possuir algum tipo de religião, semelhante ao encontrado em outros estudos. 123,127 Doutrinas religiosas podem estar associadas à adoção de comportamentos com impacto positivo nos indicadores de bem-estar psicossocial e espiritual, promovendo o apoio social, melhorando a satisfação com a vida, a qualidade de vida e um envelhecer bem sucedido. [128][129] Um estudo que objetivou identificar a correlação entre qualidade de vida e religiosidade identificou que a religiosidade está associada a maior adesão ao tratamento.…”
Section: Validação Clínica Dos Diagnósticos De Enfermagem E Seus Indi...unclassified